ANALYSIS OF THE CREATIVE THINKING ABILITY OF PGSD STUDENTS IN OPEN-ENDED PROBLEM-BASED GEOMETRY LEARNING - I Ketut Suastika; Yovita Puspasari; Sri Hariyani; Nurita Prima (JME (Journal of Mathematics Education), 2024)
Thinking creatively is an important skill in education, especially for Primary School Teacher Education Study Program (PGSD) students. This ability is crucial for understanding concepts in depth and solving problems innovatively in learning mathematics, especially geometry. However, many students still show limitations in generating creative ideas, especially in the aspects of originality and elaboration. Therefore, this research aims to analyze the creative thinking abilities of PGSD students in open problem-based geometry learning, which gives students the freedom to explore various solutions to solving geometric problems. This research uses descriptive qualitative methods with data obtained through interviews, observation, and document analysis. Research informants include lecturers, PGSD students, heads of study programs, librarians, and the curriculum development team at STKIP PGRI Trenggalek. The research results show that the open problem-based learning method effectively improves students' fluency and flexibility. However, several obstacles still required more intensive guidance and supporting technology in originality and elaboration. With the right approach, this method can be a solution to optimize students' creative thinking abilities in learning geometry.